'Anything is helpful': examining tensions and barriers towards a more LGBT-inclusive healthcare organization in the United States. Issue 4 (4th July 2022) - Table, Billy; Tronstad, L. D.; Kearns, K.
ABSTRACT: Semi-structured interviews ( N  = 34) were conducted with employees at a healthcare organization to explore their perspectives on LGBT (lesbian, gay, bisexual, and transgender) inclusion in their workplace. When lacking both comfort and a vocabulary with which to discuss issues relevant to LGBT patients and staff, employees constructed comparisons by using other groups and events as stand-ins for experiences that were unfamiliar. From employees' reflections, three dialectic tensions emerged: (1) desire for change and uncertainty about change; (2) preserving competent appearances and knowledge gap awareness; and (3) direct and indirect appraisals. The interplaying discourses that surfaced within the organization set the stage for impending inclusion initiatives. This study contributes to theorizing on dialectical tensions by examining the interplay of order and disorder activated by indirect appraisals and resistance by omission.